A systematic review of native–invasive pollinator competition in urban green space - Szilvia Kisvarga; Katalin Horotán; András Neményi; Jana Táborská; Zsanett Istvánfi; László Orlóci (Environmental Challenges, 2025)
Urbanization and climate change jointly disrupt urban vegetation by altering phenological cycles, increasing vulnerability to pests and diseases, and causing habitat fregmantation. These changes reduce essential ecosystem services—such as temperature regulation, air purification, and flood mitigation—and contribute to broader biodiversity decline. Pollinators, which rely on continuous floral resources, are especially vulnerable in urban environments. Invasive pollinator species intensify resource scarcity through exploitative behaviors (e.g., monopolizing nectar and pollen) and interference actions (e.g., aggressive exclusion), thereby reducing foraging opportunities and reproductive success among native taxa. This review synthesizes recent studies that elucidate the mechanisms underlying competition between native and invasive pollinators in urban ecosystems. We evaluate how urban policy instruments— such as integrated pest management protocols, native plant mandates, and pollinator-friendly zoning—shape vegetation composition and pollinator assemblages. Evidence shows that eradicating invasive flora, followed by the establishment of diverse native plantings, significantly elevates native pollinator richness within two years. Moreover, nesting infrastructures tailored to the life‐history traits of indigenous bees selectively enhances native recruitment while deterring exotic cavity‐nesters. Finally, we emphasize adaptive management frameworks that integrate real-time monitoring technologies (e.g., computer vision systems) and stakeholder engagement to sustain resilient pollination networks amid increasing environmental pressures. By bridging ecological theory with practical policy recommendations, this review offers a strategic framework for balancing urban development with the conservation of native pollinator communities.